What is engaging content? : influence of the social media type of message on the consumer engagement - Paraty, Tiago Carvalho Almeida Ferreira (2017)
The process of communicating with consumers has changed dramatically with the rise of social media, as social networking sites have established themselves as a legitimate, direct and free-of-charge communication channel. Considering that content is fundamental to the social media sphere, as it does not depend solely on the brands to be created, it is important to understand the pertinence, significance and impact of brand page content on Facebook. A brief look at concepts like social media, social networking sites, consumer engagement and content allowed a more congruent selection of the path chosen. By exploring the impact that seven different types of social media content have on consumer engagement regarding Facebook brand page posts, this research aims to provide relevant insights for practitioners via the identification of patterns, links and insights. In order to achieve these goals, an online survey that encompassed real Facebook brand page posts was administered and provided interesting results. The seven types of content – seasonal, activity, corporate social responsibility, customer service, product awareness, brand awareness and reward – registered different results, proving that the type of content influences consumer engagement. Moreover, corporate social responsibility was the type of content most probable to stimulate consumer engagement, followed by reward. Besides this surprising result, an overall advantage of emotional appealing types of content over informational ones, as well as differences in both age and gender groups were registered.